Position of Perma No. 1 of 2013 in the Indonesian Criminal Justice System - Danang Tri Hartono; Ainul Azizah; Nurul Ghufron (Green Publisher Indonesia, 2025)
This study examines the position of Perma No. 1 of 2013 within the Indonesian criminal justice system, focusing on its role in asset forfeiture for crimes where suspects remain at large. The research highlights the conflict between Article 79 Paragraph (1) of Law No. 8 of 2010 (Money Laundering Law), which permits in absentia trials, and the Criminal Procedure Code (KUHAP), which mandates defendant presence. Utilizing a normative juridical approach, the study analyzes legal frameworks, including the Anti-Corruption Law and Perma No. 1 of 2013, to evaluate mechanisms for confiscating assets from fugitive suspects. Findings reveal that while Perma No. 1 of 2013 provides a procedural basis for in rem forfeiture, its implementation faces challenges, particularly regarding assets outside formal accounts. The study concludes that harmonizing legal provisions and enhancing law enforcement awareness are critical to optimizing asset recovery and upholding legal certainty in Indonesia’s criminal justice system.